2021
DOI: 10.4103/jcd.jcd_182_21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autoclaving on the cyclic fatigue resistance of nickel-titanium rotary instruments: An in vitro study

Abstract: Aim: The aim of the study is to determine the effect of autoclaving on the cyclic fatigue resistance (CFR) in respect to three different rotary nickel-titanium (NiTi) systems. Methods: Three rotary NiTi files with different manufacturing process were selected and arranged into three groups. Group 1: Neolix Neoniti files ( n = 15), Group 2: Edge Files ( n = 15), Group 3: NeoendoFlex files ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Unfortunately, the process of cleaning and shaping of the canal, especially the curved canals, is not always without problems. Various studies have reported deviation of the canal path, occurrence of apical perforation, access cavity perforation, and instrument fracture within the canal [26,27,31]. Preparing an access cavity along a straight line, pre-curving of the files, and using them passively are strategies that can prevent procedural errors [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the process of cleaning and shaping of the canal, especially the curved canals, is not always without problems. Various studies have reported deviation of the canal path, occurrence of apical perforation, access cavity perforation, and instrument fracture within the canal [26,27,31]. Preparing an access cavity along a straight line, pre-curving of the files, and using them passively are strategies that can prevent procedural errors [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lot of studies, one cannot prefer one single method over others with ideal results [26]. Although previous studies have mentioned the advantages of Neolix rotary system, there are some contradictions [27]. Procedural errors in the course of treatment should be prevented to improve the prognosis of treatment [28].…”
Section: Introductionmentioning
confidence: 99%
“…Each instrument was subjected to dynamic cyclic fatigue testing in simulated stainless steel canals with a 60° angle and two radii of curvature 5 and 3 mm. [ 13 14 ] The instruments were examined under a stereomicroscope at ×10 magnification for the presence of any defect before cyclic fatigue testing. [ 5 ]…”
Section: Methodsmentioning
confidence: 99%